(untitled) (Cadernos de Ética e Filosofia Política, 2018)
Taking Claude Lefort´s arguments as a base, this article analyzes practices and representations of the two most important military organizations of Argentina, Montoneros and the Partido Revolucionario de los Trabajadores-Ejército Revolucionario del Pueblo (PRT-ERP). Those non state organizations arose during the dictatorship governments of the Revolución Argentina (1966-1973) and incorporated militants to become the two insurgent groups with greater impact and political visibility of the time. A few years later, after the rule of another dictatorship government, the so called Proceso de Reorganización Nacional (1976-1983), Montoneros and the PRT-ERP felt in a breakdown and desestructration process. Studying documents, publications, statements and practices of Montoneros and the PRT-ERP, on one hand, this article questions about how this groups represented their political internal space and how they faced diversity and division of social relations. On the other hand, we tend to show the potential of Lefort’s reflections to understand the experience of armed groups in Latin America during the second half of twentieth century.